Location-Based Handover Decision Algorithm in LTE Networks under High-Speed Mobility Scenario - Ming-ming Chen; Yan Yang; Zhang-dui Zhong (IEEE VTS Vehicular Technology Conference (1999), 2014)
This article proposes a framework of handover decision in LTE networks under high-speed mobility scenario,which is expected to support the subject's mobility at a speed of up to 500 km/h. In order to improve the handover performance in high-speed railway, a Location-Based Handover Algorithm (LBHA) is researched in this paper. The basic idea is that the vehicle speed sensor (VSS) calculates the train's distance to eNodeB (evolved Node B) by sensing its real-time velocity, and then reports the distance information to the source eNodeB periodically. Based on the location information from the train, the source eNodeB will estimate the train's relative distance to eNodeB at next reporting time, which will be further used to make handover decision in time. For better handover performance, the mobile station's location information as well as the receive signal strength has been collected to aid the handover decision. Finally, some numerical results are shown to demonstrate the effectiveness of the proposed handover decision algorithm. Compared with the traditional handover algorithm, LBHA adds 15% probability of successful handover to the traditional one, and reduces 10% probability of unnecessary handover. Furthermore, this algorithm is easy to be carried out.